Incidence of schizophrenia in ethnic minorities in London: ecological study into interactions with environment. Issue 7325 (8th December 2001) - Boydell, J; van Os, J; McKenzie, K; Allardyce, J; Goel, R; McCreadie, R G; Murray, R M
Abstract: Objective: To determine whether the incidence of schizophrenia among people from non-white ethnic minorities is greater in neighbourhoods where they constitute a smaller proportion of the total population. Design: Ecological design including retrospective study of case records to calculate the incidence of schizophrenia in the ethnic minority population across electoral wards and multi-level analysis to examine interaction between individuals and environment. Setting: 15 electoral wards in Camberwell, South London. Participants: All people aged 16 years and over who had contact with psychiatric services during 1988-97. Main outcome measure: Incidence rates of schizophrenia according to Research Diagnostic Criteria. Results: The incidence of schizophrenia in non-white ethnic minorities increased significantly as the proportion of such minorities in the local population fell. The incidence rate ratio varied in a dose-response fashion from 2.38 (95% confidence interval 1.49 to 3.79) in the third of wards where non-white ethnic minorities formed the largest proportion (28-57%) of the local population to 4.4 (2.49 to 7.75) in the third of wards where they formed the smallest proportion (8-22%). Conclusion: The incidence of schizophrenia in non-white ethnic minorities in London is greater when they comprise a smaller proportion of the local population.